Near-Infrared Spectroscopy of the Diffuse Galactic Emission. (5th March 2015) - Onaka, T.; Sakon, I.; Ohsawa, R.; Mori, T. I.; Kaneda, H.; Tanaka, M.; Okada, Y.; Boulanger, F.; Joblin, C.; Pilleri, P.
Abstract: The near-infrared (NIR) spectral range (2–5 μm) contains a number of interesting features for the study of the interstellar medium. In particular, the aromatic and aliphatic components in carbonaceous dust can be investigated most efficiently with the NIR spectroscopy. We analyze NIR spectra of the diffuse Galactic emission taken with the Infrared Camera onboard AKARI and find that the aliphatic to aromatic emission band ratio decreases toward the ionized gas, which suggests processing of the band carriers in the ionized region.